Pengembangan Prototype E-Directory Batik Berbasis Mobile Web dan Location Based-Service - Purnomo WP, Yohanes Sigit; Anindito, Kusworo; Devi Indriasari, Theresia; Suyoto, Suyoto (Jurnal Buana Informatika, 2014)
Abstract. Batik is one of Indonesian cultural works that is of high financial value, and admired by many nations in the worlds. Moreover, Indonesian Batik has been recognized by UNESCO as a non object cultural heritage in 2009. This encourages all Indonesians, not only those related to batik industries, to preserve batik. Therefore, information technology based media is needed to spread the philosophical values of batik to the community and to improve the economy for batik industries. The prototype development of mobile web and location based services of batik e - directory aims to build an information technology-based media of the philosophical values of batik to public and to improve the economy. The process includes the development of system requirements and prototype design. Requirement analysis is performed by collating appropriate information architecture to present information of e-directory and batik centers, as well as making requirement specification. The results of requirement analysis will be used as the basis to design a website prototype that can provide information about the e-directory batik and batik centers.Keywords: prototype, e-directory, batik, mobile, web, location-based serviceÂ Abstrak.Batik merupakan salah satu hasil karya budaya bangsa Indonesia yang memiliki nilai ekonomis tinggi, serta dikagumi oleh berbagai bangsa di dunia.Batik Indonesia bahkan telah diakui UNESCO sebagai warisan budaya bukan benda pada tahun 2009.Hal ini membuat batik wajib dilestarikan dan dikenal, bukan hanya oleh pelaku industri batik, tetapi juga seluruh bangsa Indonesia.Oleh karena itu dibutuhkan media berbasis teknologi informasi sebagai sarana untuk menginformasikan nilai-nilai filosofi dari batik kepada masyarakat dan sarana untuk meningkatkan perekonomian bagi pelaku industri batik.Pengembangan prototype e-directory batik berbasis mobile web dan location based-service bertujuan untuk membangun sebuah media berbasis teknologi informasi sebagai sarana untuk menginformasikan nilai-nilai filosofi dari batik kepada masyarakat dan sarana untuk meningkatkan perekonomian bagi pelaku industri batik. Proses pengembangan meliputi analisis kebutuhan sistem dan perancangan prototype. Analisis kebutuhan dilakukan dengan menyusun arsitektur informasi yang tepat untuk menyajikan informasi e-directory dan sentra batik, serta pembuatan spesifikasi kebutuhan sistem.Hasil analisis kebutuhan sistem akan dijadikan sebagai dasar bagi perancangan prototype website yang dapat menyajikan informasi tentang e-directory batik dan sentra batik.Kata kunci: prototype, e-directory, batik, mobile, web, location-based service